Chemical characterization of vetiveria Zizanioideslinn root - S.SARAVANA KUMAR,; K.GAYATHRI, (International Journal of Pharma and Bio Sciences, 2016)
Phytoconstituents are widely used for their numerous pharmacological activities. Isolation and characterization of phytoconstituents is a leading area of research. In the present study, quantitative analysis of phytoconstituents present in Vetiveria zizanoides root was carried out. GC-MS analysis of ethanolic extract from Vetiveria zizanoides (EVZ) was carried out to explore the presence of various phytoconstituents. The collected root is a rich source of macromolecules like carbohydrate, protein, and micromolecules like Vitamin C, Vitamin E and secondary metabolites like phenol, tannin, flavonoids. GC-MS spectra of EVZ shows the presence of numerous active compounds including Vetiverone (0.791%), trans-Isoeugenol(2.543%), 9,10-Dimethyltricylo[4.2.1.1(2,5)decane-9,10-dio (2.135%), Isolongifolene, 9,10-dehydro (2.182%), Tricyclo[5.1.0.0(2,4)]oct-5-ene-5-propanoic acid,3,3,8,8-tetramethyl (6.717%), 2-Naphthalenecarboxylic acid (8.884%), γ –Gurjunenepoxide(2.974%) etc., In conclusion, Vetiveria zizanoides is a rich source of phytoconstituents and numerous bioactive constituents are present in its ethanolic extract.